2021
DOI: 10.3390/pr9020295
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Flaxseed Oil—State of Art

Abstract: Microencapsulation is a well-known technology for the lipid delivery system. It prevents the oxidation of fatty acids and maintains the quality of lipid after extraction from oil seed and processing. In flaxseed oil, the amount of ω-3 and ω-6 polyunsaturated fatty acids are 39.90–60.42% and 12.25–17.44%, respectively. A comprehensive review article on the microencapsulation of flaxseed oil has not been published yet. Realizing the great advantages of flaxseed oil, information about different technologies relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 69 publications
0
14
0
2
Order By: Relevance
“…Although the cross-linked alginate-ion gel is known as a biocompatible and bioactive network with unique cell adhesion properties, it has disadvantages, such as limited durability in physiological conditions, which affects the swelling behavior and release of the drug [44][45][46]59,60]. The prepared composite gel was loaded with LOH, an extract employed in diverse medicine for its biologically active compounds [36,37,61,62]. According to Wang et al, several intermolecular cross-links may be formed through Ca 2+ between nHA and Alg, LOH and Alg, and nHA and LOH due to the divalent nature of Ca ions [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the cross-linked alginate-ion gel is known as a biocompatible and bioactive network with unique cell adhesion properties, it has disadvantages, such as limited durability in physiological conditions, which affects the swelling behavior and release of the drug [44][45][46]59,60]. The prepared composite gel was loaded with LOH, an extract employed in diverse medicine for its biologically active compounds [36,37,61,62]. According to Wang et al, several intermolecular cross-links may be formed through Ca 2+ between nHA and Alg, LOH and Alg, and nHA and LOH due to the divalent nature of Ca ions [35].…”
Section: Discussionmentioning
confidence: 99%
“…Wall materials, such as polysaccharides (alginate, carboxymethylcellulose, arabic gum, maltodextrin, hydrophobically modified starch) and proteins (whey protein, soy protein, sodium caseinate, gelatin) are used to prepare microcapsule by spray drying technique [31,36,40]. It has been reported that the size of the microcapsule, prepared by spray drying process ranges within 10-400 µm [50]. The particle size of microcapsule is influenced by the type of atomizer, such as centrifugal wheel atomizer and spray pressure nozzle.…”
Section: Spray Dryingmentioning
confidence: 99%
“…If the spray pressure nozzle is used, the particle size of spray-dried product is increased with increase of the nozzle orifice diameter and decreased by the atomization pressure. When the centrifugal wheel atomizer is used, larger wheel diameter and speed provide a smaller size of the particle [32,50]. Furthermore, different process parameters in emulsion preparation and drying process influence the particle size of microcapsule.…”
Section: Spray Dryingmentioning
confidence: 99%
See 2 more Smart Citations